KARAKTERISTIK PENYAKIT TUBERKULOSIS (TBC) PARU - Asmirati Yakob; Lina Alfiyani; Avi Arya Buana Jaya Putra (Akbid Wirabuana, 2023)
Tuberculosis (TB) is an infectious disease that is mostly caused by mycobacterium tuberculosis germs.This disease generally causes signs and symptoms that vary greatly in each sufferer, ranging from asymptomatic to very acute symptoms. The purpose of this study is to determine the characteristics of Pulmonary Tuberculosis (TB) at Manguharjo Madiun Lung Hospital in 2023. The research design used in this study is Descriptive. The population in this study was all outpatients diagnosed as TB sufferers, this study was conducted at the Manguharjo Lung Hospital in Madiun. Sample selection is done by 'purposive sampling', and meets the 'inclusion and exclusion criteria. The variables in this study used a single variable, namely the characteristics of pulmonary TB patients (gender, age, education, health insurance and occupation). The data collection technique used is primary data taken at the time of research. Based on the characteristic research of tuberculosis patients at Manguharjo Madiun Lung Hospital, it can be concluded that the characteristics seen from the age of the patient and male gender, who are more than 38 years old, higher education, and IRT (Housewife) work are characteristics of patients who come to visit the hospital.Keyword : Characteristics, Tuberculosis